Land-use change in Changli County, China: Predicting its spatio-temporal evolution in habitat quality. (October 2020) - Tang, Feng; Fu, Meichen; Wang, Li; Zhang, Pengtao
Highlights: Our method can accurately predict future land-use change and habitat quality. Prediction from CA-Markov and CLUE-S has obvious differences in small partial areas. Construction land continues to expand while other land types continue to decline. Land-use change has a large effect on regional habitat quality change. The future habitat quality will continue to degrade in Changli County. Abstract: Rapid urbanisation and expansion of residential, industrial, and traffic areas have greatly changed regional land-use patterns and have directly affected habitat quality and biodiversity. Assessing and predicting the spatio-temporal evolution and future development trends of habitat quality under the influence of land-use change can provide a scientific basis for regional natural environment conservation and land-use planning. To calculate land-use patterns across space and time, we used different data sources including land-use change surveys, meteorology, statistical yearbooks, and digital elevation model data in Changli County. We modelled past, present and future land-use change with two different models (Cellular automata-Markov and CLUE-S) and integrated them separately to habitat quality modelling using the integrated valuation of environmental services and trade-offs model. With this we aimed to provide a reference for future implementations of ecological restoration work and adjustments of land-use policies for decision-makers. The estimations showed that habitat quality declined from 2004 to 2028 because of the continuous increase in residential land and traffic area, whereas other land types continued to decline. Furthermore with this study we provide a new method for monitoring and simulating habitat quality.